Designing the Future: How Engineering Builds Creative Critical Thinkers in the Classroom (Boost Critical and Creative Thinking Using the Engineering Design Process) - Kaiser, Ann (Solution Tree Press, 2019)
No matter the subject or grade, giving students engineering design process challenges encourages creativity, communication, innovation, and collaboration. In Designing the Future, author Ann Kaiser outlines how to enhance -- not increase -- what you are already teaching by implementing the engineering design process. Throughout the book, you will find more than 25 easy-entry, low-risk activities and projects you can begin incorporating into existing classwork. Use the engineering design process for students to transform creative and critical-thinking classroom activities: * Explore the engineering design process (EDP) and unpack its stages: problem definition, research, brainstorming, prototyping, testing, and optimizing. * Understand how incorporating engineering for students creates a project-based learning environment that encourages essential 21st century skills, including creativity, innovation, and critical thinking. * Empower students to embrace the fundamentals of engineering design thinking, including: there is always more to learn, your solution will create problems, and there is no one right answer. * Learn how to develop and adapt engineering design process projects for various grade levels and disciplines. * Receive reflection tools that will empower you to revise and re-engineer activities and projects. * Incorporate elements of engineering and STEAM education lesson plans into your current classroom content. Contents: Introduction Part I Chapter 1: Building an Engineering Design Culture Chapter 2: Deconstructing the Engineering Design Process Chapter 3: Designing Projects Part II Chapter 4: Starting With Activities That Support Engineering Thinking and Skills Chapter 5: Introducing Projects for Elementary School Chapter 6: Introducing Projects for Middle and High School Part III Chapter 7: Reflecting On, Revising, and Optimizing Your Curriculum Epilogue Appendix A: Action Plan Summary Appendix B: Challenge Creation Appendix C: Engineering Notebook Forms References and Resources Index